AKIBAT HUKUM PERCERAIAN PADA PERKAWINAN ERDEMU IMPAL (STUDI DI KELURAHAN LAU CIMBA KECAMATAN KABANJAHE KABUPATEN KARO SUMATERA UTARA) - FICA INDIKA TAMIN DAMANIK (PREMISE LAW JURNAL, 2017)
Erdemu impal marriage is an adat marriage in the Karo community in which the bride has the same impal kin (the daughter of the groom’s uncle who is his mother’s brother). This marriage is favored by the Karonese community because of dome reasons: the inheritance will be received only by their relatives, keep the kinship in the big relatives, and there are some worries about the looseness of kinship in the big family when a girl gets married with a man who is not close to the family so that there will be conflicts in the family. The research used juridical empirical and descriptive analytic method; the result of this research was expected to provide complete and systematic description on the legal consequence of divorce in the ‘erdemu impal’ marriage. At Kelurahan Lau Cimba, Kabanjahe Subdistrict, Karo Regency, North Sumatera. The result of the research showed that this type of marriage is performed in adat (custom), and it is not registered in a legal Marriage Institution. In reality, marriages which occur at Kelurahan Lau Cimba, Kabanjahe, Karo Regency, have no divorce since this type of marriage does not recognize divorce (mulih) since the bride and the groom are still close relationship. If there is a divorce, it is because of death which seperate them, and it is in accordance with the religious doctrine. The legal consequence of marriage is the same clan with what happens with the other marriages when they are in accordance with religion, adat, and the prevailing regulations. When there is disharmony in this marriage, it will be settled by the family and relatives of both husband and wife until the adat leader. The solution is settled by two methods guncih abu and kawin gantung.. Keywords: Divorce, Erdemu Impal Marriage, Legal Consequence